Building a National Culture of Health Background, Action Framework, Measures, and Next Steps - Chandra, Anita (RAND Corporation, 2016)
In 2013, the Robert Wood Johnson Foundation (RWJF) embarked on a pioneering effort to advance a Culture of Health initiative. A Culture of Health places well-being at the center of every aspect of life, with the goal of enabling everyone in our diverse society to lead healthier lives. To implement this vision, RWJF worked with RAND to develop an action framework that identifies how the nation will work toward achieving these outcomes.